Answer: Choice D
HG= 11 square root 3/3 and HI = 22 square root 3/3
In other words,
![\text{HG} = (11√(3))/(3) \ \text{ and } \ \text{HI} = (22√(3))/(3)\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/5kc0i340pdgkb0kkkpct4fhacrwez6k8pc.png)
==========================================================
Step-by-step explanation:
Let's say that x is the short leg and y is the long leg
For any 30-60-90 triangle, we have this connection:
![y = x√(3)](https://img.qammunity.org/2022/formulas/mathematics/college/fpw6jsy2bktcmfdnmh1ch0t3zsg2rvffce.png)
The long leg y is exactly sqrt(3) times longer compared to the short leg x.
Let's solve for x and then plug in y = 11
![y = x√(3)\\\\x = (y)/(√(3))\\\\x = (y*√(3))/(√(3)*√(3))\\\\x = (y√(3))/(3)\\\\x = (11√(3))/(3)\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/4q7w0dxnib8byz4m06cnooeojrvywnpewd.png)
Side HG, the shorter leg, has an exact length of
![\text{HG} = (11√(3))/(3)\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/7igkamv8tjbiy8toqlvbhjoelo16ty1p9f.png)
------------------
Once we know the short leg, we double that expression to get the length of the hypotenuse. Like before, this only applies to 30-60-90 triangles.
![\text{hypotenuse} = 2*(\text{short leg})\\\\\text{HI} = 2*\text{HG}\\\\\text{HI} = 2*(11√(3))/(3)\\\\\text{HI} = (22√(3))/(3)\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/5ih1tmtvob2aoxo58noftjiuuikl8h9iqz.png)
------------------
Since
and
, this shows that choice D is the final answer.